2014
DOI: 10.1039/c4cy00411f
|View full text |Cite
|
Sign up to set email alerts
|

Polycondensation of guanidine hydrochloride into a graphitic carbon nitride semiconductor with a large surface area as a visible light photocatalyst

Abstract: g-C3N4 prepared from guanidine hydrochloride exhibited a large surface area and a reduced recombination rate of electrons and holes, leading to improved photocatalytic activity for degrading RhB under visible light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 45 publications
1
65
0
Order By: Relevance
“…[21][22][23][24]39,40 Additionally, the additional weak diffractions situated at about 17.6 and 22.2° can be attributed to (600) and (650) planes of graphitic carbon nitride, respectively, which results from the denser packing or a distortion of the melon structure in which every second melon sheet is displaced. 41 Notably, the overall weakened intensity is examined for P-CN, indicating that doping P into the g-C 3 N 4 network can significantly reduce the correlation length of interlayer periodicity and particle size, correlating well with the TEM observation. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 …”
Section: Resultsmentioning
confidence: 72%
“…[21][22][23][24]39,40 Additionally, the additional weak diffractions situated at about 17.6 and 22.2° can be attributed to (600) and (650) planes of graphitic carbon nitride, respectively, which results from the denser packing or a distortion of the melon structure in which every second melon sheet is displaced. 41 Notably, the overall weakened intensity is examined for P-CN, indicating that doping P into the g-C 3 N 4 network can significantly reduce the correlation length of interlayer periodicity and particle size, correlating well with the TEM observation. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 …”
Section: Resultsmentioning
confidence: 72%
“…It was reported that g-C 3 N 4 showed good photocatalytic performance for H 2 evolution via water splitting and degradation of organic pollutants [13][14][15][16][17][18][19][20][21]. However, its poor light absorption performance and easy recombination of electron-hole pairs limited the photocatalytic efficiency of g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 97%
“…For the purpose of taking full advantage of solar energy, a great number of semiconductor materials with visible light activities have been exploited [1][2][3]. As a typical metal-free polymeric semiconductor material, graphitic carbon nitride (g-C 3 N 4 ), has attracted great scientific interest due to its suitable band gap to absorb the visible light and unique properties, such as excellent performance of hydrogen production from water splitting and degradation of organic pollutants under visible light irradiation [4][5][6][7][8][9][10][11][12][13]. Unfortunately, the efficiency of bulk g-C 3 N 4 was still restricted due to the high recombination rate of photogenerated electron-hole pairs and low surface area (less than 10 m 2 g −1 ).…”
Section: Introductionmentioning
confidence: 99%